1
$\begingroup$

Solve this equation: $$3^{\log_{4}x+\frac{1}{2}}+3^{\log_{4}x-\frac{1}{2}}=\sqrt{x}\qquad (1)$$

I tried to make both sides of the equation have a same base and I started:

$$(1)\Leftrightarrow 3^{\log_{4}x}.\sqrt{3}+ \frac{3^{\log_{4}x}}{\sqrt{3}} = \sqrt{x}$$ $$\Leftrightarrow 3^{\log_{4}x}.3+ 3^{\log_{4}x} = \sqrt{3x}$$ $$\Leftrightarrow 4.3^{\log_{4}x}= \sqrt{3x}$$

At this step, I can't continue. Please help me!

$\endgroup$
1
$\begingroup$

First of all impose the necessary existence conditions, that is: $x > 0$ for the logarithms and $x \geq 0$ for the square root. That is, eventually,

$$x > 0$$

for the whole equation.

Then follow Siong Thye Goh reasoning, obtaining the final equation he wrote.

At that point:

$$1 + \log_4(3)\log_4(x) = \frac{\log_4(3)}{2} + \frac{\log_4(x)}{2}$$

$$\log_4(x)\left(\log_4(3) - \frac{1}{2}\right) = \frac{\log_4(3)}{2} - 1$$

$$\log_4(x) = \frac{\frac{\log_4(3)}{2} - 1}{\log_4(3) - \frac{1}{2}} = \frac{\log_4(3)-2}{2\log_4(3)-1}$$

To solve for $x$ take the exponential base 4 of both terms, getting:

$$\large x = \large 4^{\frac{\log_4(3)-2}{2\log_4(3)-1}}$$

$\endgroup$
4
$\begingroup$

Guide:

Taking $\log_4$ on both sides,

$$1 + \log_4 3 \cdot \log_4 x = \frac12 (\log_43 + \log_4 x)$$

Solve for $\log_4 x$.

$\endgroup$
0
$\begingroup$

You may also continue as follows:

$$\begin{eqnarray*} 4 \cdot 3^{2 \cdot \log_{4}\sqrt{x}} &= & \sqrt{3}\sqrt{x} \Leftrightarrow \\ 4 \cdot 9^{\log_{4}\sqrt{x}} &= & \sqrt{3}\sqrt{x} \Leftrightarrow \\ 4 \cdot 4^{\log_4{9} \cdot \log_{4}\sqrt{x}} &= & \sqrt{3}\sqrt{x} \Leftrightarrow \\ (\sqrt{x})^{\log_4{9} -1} &= & \frac{\sqrt{3}}{4} \Leftrightarrow\\ x & = & \left( \frac{\sqrt{3}}{4}\right)^{\frac{\log_4{9}-1}{2}} \approx 0.0571725 \end{eqnarray*}$$

$\endgroup$
0
$\begingroup$

Let's generalise a bit, with parameters say $a, b \in (0, \infty)\setminus \{1\}$ subject to $a^2 \neq b$ and let's try to solve the equation:

$$a^{\log_{b}x+\frac{1}{2}}+a^{\log_{b}x-\frac{1}{2}}=\sqrt{x}$$

Notice that the left-hand side can be rewritten as

$$a^{\log_{b}x}(\sqrt{a}+\frac{1}{\sqrt{a}})=b^{\log_{b}a\cdot \log_{b}x}(\sqrt{a}+\frac{1}{\sqrt{a}})=x^{\log_{b}a}(\sqrt{a}+\frac{1}{\sqrt{a}})$$

As you are dealing exclusively with strictly positive reals, your given equation is equivalent to its square, so to speak:

$$\frac{(a+1)^2}{a}x^{2\log_{b}a}=x$$

which leads to

$$x^{2\log_{b}a-1}=\frac{a}{(a+1)^2}$$

Since the right-hand side is never $1$ (you can try to see why), this is why we initially imposed the relation of inequality between $a$ and $b$; it is satisfied in the particular case of your equation.

We finally have the solution:

$$x=\left(\frac{a}{(a+1)^2}\right)^{\frac{1}{2\log_{b}a-1}}$$

$\endgroup$
0
$\begingroup$

Same solution with same approach But simplified with substitution Solution

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.